A dictionary of physics - Daintith, John. ([S.l.] : Oxford University Press, 2010)
This classic desktop reference has been thoroughly revised, bringing readers more than 3,800 entries--200 new to this edition--that define the terms of this fast-changing field with clarity and without jargon. The author provides coverage of all areas of physics and many related fields, including astronomy, astrophysics, and physical chemistry. He offers expanded information on applied physics, statistical distributions, polymers, and nanoscience, and includes ten feature articles on such key topics as crystal defects, magnetic resonance imaging, and the solar system. Here, too, are detailed appendices on SI units and the electromagnetic spectrum, a timeline of key dates in physics, a list Nobel Prize winners, and much more. And, as with all Oxford dictionaries, this volume offers abundant web links, kept up to date on the Dictionary of Physics companion web page. Featuring more than 120 diagrams, graphs, and tables, this is a superb resource for students, teachers, and professional physicists.
Keywords: physics,physics dictionary